Defending victims of cyberbullying: The role of self-efficacy and moral disengagement. (February 2020) - Bussey, Kay; Luo, Aileen; Fitzpatrick, Sally; Allison, Kimberley
Abstract: Cyberbullying is a significant problem worldwide that affects adolescents' social relations, academic achievement, and mental health. As this form of bullying is typically viewed by a large audience it is important to understand the role of observers as they may hold a key for reducing bullying. The aim of this study was to investigate the role of the socio-cognitive factors of defending self-efficacy (i.e., belief in one's capability to defend) and moral disengagement (i.e., justifications for aggressive behavior) associated with general cyber defending behavior and cyber defending response types: constructive and aggressive. Participants were 540 male and female students of diverse racial identity between the ages of 11 and 15 years who completed a questionnaire comprising multiple measures. Regression analyses revealed that at low levels of defending self-efficacy, moral disengagement was unrelated to general cyber defending behavior. However, at high levels of defending self-efficacy, moral disengagement was positively associated with general cyber defending. Further regression analyses revealed that the results for constructive cyber defending were the inverse of those obtained for aggressive defending. Defending self-efficacy was positively associated with constructive defending and negatively associated with aggressive defending. Moral disengagement was negatively associated with constructive defending and positively associated with aggressive defending. These results address the perplexing issue of why moral disengagement has been related to defending in some studies and not in others. As with most measures of defending, the general cyber defending measure confounds constructive and aggressive defending.